The Elements of health-related physical fitness in children with Down syndrome. A comparative study between practitioners and non-practitioners of adapted physical activities - جالم محمد; مويسي فريد; سبع بوعبد الله (Journal of Sport Science Technology and Physical Activities, 2022)
The study aimed to identify the level of some elements of physical fitness related to health between children with Down syndrome who practice and those who do not practice adapted physical activities through the application of a battery of tests. For the benefit of children practicing air-conditioned physical activities